2020
DOI: 10.1007/s11365-020-00682-x
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise risk management in small and medium family enterprises: the role of family involvement and CEO tenure

Abstract: Taking the right amount of risk is essential for successful business. As a response to the importance of risk management, the effectiveness and implementation of enterprise risk management (ERM) systems are recently discussed in literature. However, smaller firm entrepreneurs often deal with this challenge in practice in a more informal way. Most of these small and medium-sized enterprises (SME) are family firms, where family dynamics further influence their risk behaviour. Addressing the missing implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 85 publications
2
23
1
Order By: Relevance
“…on risk-taking (Daniell & Hamilton, 2010). Our study complements previous research, namely that families should maintain entrepreneurial orientation in the business when moving through different generations as generations bring new perspectives to the business (Glowka et al, 2020).…”
Section: Resultssupporting
confidence: 70%
“…on risk-taking (Daniell & Hamilton, 2010). Our study complements previous research, namely that families should maintain entrepreneurial orientation in the business when moving through different generations as generations bring new perspectives to the business (Glowka et al, 2020).…”
Section: Resultssupporting
confidence: 70%
“…Some research has already found such training to be important for applying more sophisticated risk management approaches (Beasley et al, 2015). In addition, there is initial evidence that top manager characteristics such as the CEO's tenure, ownership stake, locus of control and risk-taking propensity, as well as the CRO's education and career trajectory can help explain why some organizations feature more sophisticated risk management systems than others (Bailey, 2019;Glowka et al, 2021;Hiebl et al, 2019;Ludin et al, 2017;Paape and Speklé, 2012). However, the findings on how other characteristics of top managers such as CEOs, CFOs and CROs, as well as entire top management teams influence change in risk management and risk governance are still missing.…”
Section: Future Research On Risk Governance and Risk Management In Changementioning
confidence: 99%
“…TFB are often centered on a vision which places personal or family needs and preferences ahead of growth and profit maximization [7,42], yet this presents them with specific challenges for entrepreneurship [43] and inheritance [44,45]. This feature is directly related to the fact that the majority of TFB are SMEs or even micro businesses [7,46], and the founder is still the owner and director [10,13,47,48]. Specifically, in the study by Kallmuenzer et al [46], nearly 70% of surveyed firms from Western Austria, Vorarlberg, Tyrol, and Salzburg are small firms with fewer than 49 employees.…”
Section: Family Business Objectives and Characteristic Behaviors Of Family Owners And Managementmentioning
confidence: 99%
“…Given that the development of resources and capabilities is the result of business decisions, the analysis of the germination process requires analysis of the specific features of the bodies in which responsibility and decision-making power rests. Agency theory points to the ownership structure as a determinant of the company's behavior, since its profile has important consequences for decision-making, exploitation of opportunities, resource and capabilities development, and attitude towards risk [48,136,137]. Therefore, we recommend that researchers consider: RQ6: What ownership and control structures, related to family involvement, are the most suitable for promoting dynamic capabilities and innovation performance in TFB?…”
Section: An Integrative Framework For Studying Tourist Family Businessesmentioning
confidence: 99%